PENGARUH KOMPENSASI TERHADAP KINERJA GURU TIDAK TETAP (GTT) DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi pada SD Negeri di Kabupaten Temanggung) - Kartikaningrum, Ita; Nugraheni, Rini (Diponegoro Journal of Management, 2020)
This research aims to examine the effect of compensation on teacher performance through work motivation as an intervening variable on the primary schools Temanggung regency area. This study uses the independent variable that is compensation, the intervening variable that is work motivation, and the dependent variable that is teacher performance. The sample in the study was elementary school teachers in the Temanggung Regency which consisted of 20 districts. The sampling technique was conducted by purposive sampling method. Collecting data was conducted by a questionnaire distributed directly to 100 elemtary school teachers. The data analysis technique used in this study is Partial Least Square with SmartPLS 3.2.9 apllication to determine the path coefficient, and the direct or indirect effect of independent variable on dependent variable. The result of this reseach showed that compensation had a positive and significant effect on teacher performance and work motivation. Work motivation had a positive and significant effect on teacher performance. In addition, work motivation variables can mediate an indirect relationship between compensation on teacher performance.